Task technology fit in online transaction through apps - Valaei, Naser *; Nikhashemi, Seyedrajab *; Hwang, Ha Jin *; Dent, Michael M * (IGI Global, 2018)
The purpose of this chapter is to examine what aspects of task-technology characteristics are most relevant to fit, satisfaction, and continuance intention of using apps in mobile banking transactions. Applying the SEM approach to a sample of 250 Malaysians, the findings of this chapter imply that the task characteristic of transaction-based apps is more relevant than technology characteristics. The results suggest that degree of fit is highly associated with mobile apps user satisfaction. Furthermore, the higher the degree of fit, the higher is the continuance intention to use apps for online transactions. Surprisingly, the findings show that the task characteristics are not relevant to continuous intention to use apps for online transactions.